The Utility of the Novel Hematologic Parameters for Predicting in Hospital Mortality in Patients with Acute Mesenteric İschemia - Süleyman Sezai YILDIZ; Murat AVŞAR; Gülçin ERCAN; Serhat SIĞIRCI; Gökhan AKSAN; Hakan KİLCİ (Bezmiâlem Science, 2019)

(untitled)
Objective:Acute mesenteric ischemia (AMI) is recognized as a vascular emergency, having high mortality and requiring rapid and efficient and treatment. In this study, we aimed to assess the levels of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in patients with AMI and to search for a relationship between the NLR and PLR values and inhospital mortality of patients with AMI.Methods:In total, one hundred and twenty three patients (67 AMI+ and 56 AMI-) were included in this retrospective study. Sixty seven patients diagnosed as having AMI following computed tomography angiography after presenting to the emergency room were included in AMI (+) group. “Receiver Operating Characteristic” analysis was done to determine the optimal NLR and PLR thresholds in diagnosis and inhospital mortality of AMI. Also, univariate and multivariate analyses were made to evaluate the complete blood count parameters affecting the outcomes of patients with AMI.Results:It was found that AMI+ patients had higher neutrophil count than AMI- patients, while the lymphocyte count was significantly lower (p<0.001 p<0.001, respectively). The NLR and PLR values were significantly higher in AMI+patients than in AMI–patients (p<0.001, p<0.001, respectively). In the multiple logistic regression analysis, only NLR and red cell distribution width were identified as independent predictors of inhospital mortality of patients with AMI [Odds ratio (OR)=1.171, 95% confidence interval (CI)=1.020-1.345, p=0.026; OR=1.474, 95% CI=1.028-2.113, p=0.035, respectively]. Although PLR failed to predict inhospital mortality in AMI+ subjects (area under the curve (AUC=0.597, 95% CI=0.459-0.734, p<0.178), NLR level greater than 10.1, measured on admission, predicted inhospital mortality in AMI+ subjects (AUC=0.698, 95% CI=0.570-0.827, p<0.006).Conclusion:Neutrophil-to-lymphocyte ratio is a reliable predictive marker in hospital mortality in patients with AMI.